El paradigma de las concepciones alternativas y la formación de los profesores de ciencias - Vázquez Alonso, Ángel (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
The pre -service education of science teachers is empirically studied in the framework provided by the paradigm of alternative conceptions by means of 13 simple usual Physics questions. The rates of pre -service teachers' alternative conceptions show a strong resemblance with those found in previous research even with students. Differences between sex and age groups are remarkable, but the major finding is that only physicists show a suitable pattern lacking alternative conceptions about Physics topics, while other science careers not only have a lot of alternative conceptions but also science and non -science teachers show similar patterns. We claim a pre -service teacher education more based on conceptual change aimed to avoid teachers' alternative conceptions in basic science contents of different areas.